(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In this work, seed productivity indicators and their determinants in lemon cultivars were studied, including floral biology, pollination, fertilization efficiency, and internal fruit structure. The studies were conducted on the basis of phenological records, fruit and seed morphometry, seed quality indicators, and laboratory germination tests. The results obtained revealed differences in seed productivity and seed quality specific to cultivars. The results serve as a scientific basis for selecting propagation material.